Interpreting services in the European Union's institutions - Opara, Agata (elingUP: Revista Eletrónica de Linguística dos Estudantes da Universidade do Porto, 2017)
The origins of the profession of simultaneous interpretation are traced in the ancient times. However, it was not until a century ago that interpreting started to be associated with a professional status. A turning point in the modern history of international interpreting was marked by Paul Mantoux's interpreting for the Allied leaders at the Paris Conference in 1919. His brilliant performance influenced a transition from chance interpreters to adequately skilled professionals working at the League of Nations and the International Labour Office in Geneva. Incorporating specific technical subjects during international discussions contributed to the need for expert linguists. This led to the establishment of the first School for Interpreters in Geneva in 1941 which trained the candidates in whispering and consecutive interpreting.